Six-legged mobile robot - Chua, Jerome (Animo Repository, 2000)
Mobile robots have two major methods of mobility: wheels and legs. Wheeled vehicles provide a stable base for the robot, however they require a relatively flat and hard surface on which to maneuver. Research on legged robots promises to overcome this difficulty. Legged robots have the ability to maneuver over rough terrain due to the active suspension of its legs that is, its legs have a discontinuous contact with the ground. Because of the dynamic potential that legged robots possess, applications are being developed and are taken advantage of by many industries. The objective of this thesis is to developed and test a six-legged mobile robot. It is capable of walking forward, background, turning right and left through different walking patterns namely: tripod, oar, and wave gait. Each leg requires two degrees of freedom needed for the lifting and sweeping motions of the robot, as provided for by the servomotors. The Serial Servo Controller (SSC) controls the movement of the servomotors based on instructions received from the host computer. The robot is designed to be a stable platform for possible improvements to its current capabilities. Obstacle detection and video capture systems are examples of enhancements implemented in the robot.